First molecular detection of Neospora caninum in feces of grey wolf (Canis lupus) and golden jackal (Canis aureus) populations in Slovenia - Bandelj, Petra; Kušar, Darja; Šimenc, Laura; Jamnikar Ciglenečki, Urška; Vengušt, Gorazd; Žele, Diana (Animals, 2023)
Neospora caninum is an obligate intracellular parasite that causes reproductive disorders and major economic losses in cattle, and induces neuromuscular disorders in canids. Exogenous infections are becoming increasingly important due to disease outbreaks. The sylvatic life cycle of N. caninum interferes with the domestic dog-ruminant life cycle, but understanding of it is scarce. The population of wild canids may play an important role in parasite dispersion. Feces from 42 grey wolves (Canis lupus) and 39 golden jackals (Canis aureus) were analyzed for the N. caninum Nc5 gene using a novel real-time PCR (qPCR) with a detection limit of 5 targets/µL in clinical samples. Three wolves (3/42 7.1%) and one golden jackal (1/39 2.6%) tested positive, which is the first detection of N. caninum in the population of grey wolves in Slovenia and the first detection of N. caninum DNA in the feces of a golden jackal. In addition to the grey wolf, we propose the golden jackal as a potential definitive host with hypothetical epidemiological importance for the sylvatic-domestic life cycle of N. caninum, due to its proximity to human habitats and its rapid expansion throughout Europe.